Factors associated with regional retention of physicians: a cross-sectional online survey of medical students and graduates in Japan - Soichi Koike; Kentaro Okazaki; Akiko Tokinobu; Masatoshi Matsumoto; Kazuhiko Kotani; Hitomi Kataoka (BMC, 2023)
Abstract Background Physician shortage and maldistribution is an urgent health policy issue requiring resolution. Determination of factors associated with regional retention and development of effective policy interventions will help to solve this issue. The purpose of the present study was to identify factors associated with regional retention and discuss their policy implications. Methods We conducted a cross-sectional online survey from February to March of 2022 for graduates from regional quotas (special quotas for medical schools to select students engaged in community medicine) and Jichi Medical University (JMU) and students at 10 medical schools including JMU. Completed surveys were obtained from 375 graduates and 1153 students. Questions included intention to continue to work in their home prefecture in the future, as well as background information and potential factors associated with regional retention. In the analyses, regional quotas and JMU were referred to as community medicine-oriented programs and schools (CMPS). We performed logistic regression analyses to identify factors associated with regional retention. Results Among the students, scholarship-bonded obligatory service, satisfaction with current life, intention to belong to ikyoku (a traditional physician allocation/training system in Japanese medical schools), and interest in general practice/family medicine were significantly positively associated with regional retention. Among the graduates, satisfaction with training environment, intention to belong to ikyoku, and recommending their program to high school students were significantly positively associated with regional retention. For students of CMPS, satisfaction with the career development program was positively associated with future regional retention. For graduates, this association was observed only in the crude analysis. Conclusions In addition to known factors such as interest in general practice/family medicine, intention to belong to ikyoku had a substantial impact on regional retention. The present results suggest that the career support system represented by ikyoku as well as a career development program are of potential importance for increasing regional retention through the mechanisms of a sense of belonging and a life-long education system. These findings provide useful information for the development of further policy interventions that interweave traditional and new systems to maximize their effectiveness.